دراسة قياسية لأثر مؤشرات السيولة على ربحية البنوك الجزائرية خلال الفترة 2012-2017 - بوهرين, فتيحة (جامعة الوادي - University of Eloued, 2022)
This study aims to identify the impact of liquidity indicators on the profitability of a selected sample of Algerian commercial banks during the years (2012-2017), by conducting an analytical standard study. For the purposes of achieving the objective of the study, the eviews9 program was used, and this was done by using temporal cross-sectional data. The study found that there is a difference between banks in the impact of liquidity indicators, both with regard to the return on assets or the return on equity in the fixed limit..
A record study of the impact of liquidity on profitability in banking sector of Algeria during 2012-2017
مقال
Keywords: مؤشرات؛ السيولة؛ الربحية؛ البنوك: Indicators; liquidity; profitability; banks.